The Potential Development of Pararem for Tobacco Control in Dalung Village Badung Regency - Kurniati, Ni Made; Astuti, Ni Putu Widya; Purnawan, I Nyoman; Primatanti, Putu Asih; Kharisma, Putu Anastasia; Sumadewi, Ni Luh Utari; Suarjana, Nyoman; Komang Sriwisani S (LPPM Universitas Dhyana Pura, 2025)
Places of worship and public spaces are areas located within traditional village environments and are regulated under the No Smoking Area (KTR) Regional Regulation at both the Bali Province and Badung Regency levels. Most community activities, particularly among the Balinese population, take place within traditional village settings. This study aims to explore the potential for developing pararem (customary rules) to control the dangers of smoking in Dalung Village, an urban-area village with various activities held in places of worship and public spaces. This qualitative research explores the potential for developing Pararem to control smoking hazards in Dalung Village. Community leaders in Dalung stated that smoking is still frequently observed during religious ceremonies and public activities in the village. All respondents perceived that smoking behavior in the community negatively impacts the health of non-smokers. Pararem has strong potential to be developed as a more binding and respected form of smoking control in villages. With support from the government, relevant institutions, and academics, the development of pararem can begin. However, the process of formulating and aligning it with the provisions of the awig-awig (village customary laws) requires a lengthy process and consensus from village residents.